Implementation of the Principles of Islamic Educational Communication in the Qur'an in the Formation of Students' Religious Character - S, Mahfud; Das, St. Wardah Hanafie; Mangsi, Raya; Kulle, Syarifuddin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
This research aims to: (1) describe the principles of Islamic educational communication in Surah Luqman verses 12–19; (2) reveal the form of its implementation in the learning process at MAN Bontang; (3) analyze the challenges faced by teachers and schools in integrating Qur'anic communication principles; and (4) assess the impact of the application of these principles on the formation of students' religious character. The research uses a qualitative method with a case study approach. Primary data sources include madrasah heads, teachers, and students, while secondary data comes from school documents and archives. The research instrument is the researcher, supported by interview guides, observations, and documentation. Data were collected through in-depth interviews, participatory observations, and documentation studies, then analyzed using the Miles & Huberman model (data reduction, data presentation, conclusions/verification) and validated through triangulation. The results of the study show that the principle of communication of Islamic education in Surah Luqman verses 12–19 forms the religious character of students through the strengthening of monotheism, gratitude, respect for parents, amar ma'ruf nahi munkar, patience, and social ethics. Its application is carried out integratively through the communication pattern of qaulan (sadidan, balighan, layyinan, ma'rufan, kariman) by teachers as a moral example. The main challenges stem from internal factors of students and the influence of popular culture. As a result, students show spiritual awareness, moral discipline, social politeness, and responsible communication skills. This research confirms that Qur'anic education is able to form kamil people holistically in the modern era.